2018
DOI: 10.1007/s10926-018-9806-6
|View full text |Cite
|
Sign up to set email alerts
|

Employers’ Perspectives on Accommodating and Retaining Employees with Newly Acquired Disabilities: An Exploratory Study

Abstract: Introduction Timely and appropriate accommodations can help employees who experience disabilities stay at work instead of exiting the labor force. Employers can play a critical role in connecting such workers with the accommodations they need. This qualitative study seeks to inform policy makers who want to improve workforce retention outcomes by uncovering factors that affect whether employers provide accommodations to, and ultimately retain, employees with disabilities. Methods We conducted semistructured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Disability disclosure rates amongst people with disabilities are low, which is concerning because they have to disclose their needs to receive workplace accommodations (Lindsay et al, 2013;Maestas and Mullen, 2019). Thus, efforts to improve workplace disability disclosure are critical because non-disclosure could lead to unsafe working conditions, poor job performance and affect overall well-being (Nevala et al, 2015;Gould-Werth et al, 2018). Additionally, our findings aligned with other research, showing that some employers may be uncomfortable around people who have a disability, and therefore it is important to find ways to minimize such discomfort because it can lead to stigma and discrimination (Lyons et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disability disclosure rates amongst people with disabilities are low, which is concerning because they have to disclose their needs to receive workplace accommodations (Lindsay et al, 2013;Maestas and Mullen, 2019). Thus, efforts to improve workplace disability disclosure are critical because non-disclosure could lead to unsafe working conditions, poor job performance and affect overall well-being (Nevala et al, 2015;Gould-Werth et al, 2018). Additionally, our findings aligned with other research, showing that some employers may be uncomfortable around people who have a disability, and therefore it is important to find ways to minimize such discomfort because it can lead to stigma and discrimination (Lyons et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…Employers and managers could aim to create an inclusive and safe environment by communicating the organizational values and diversity policies and ensuring the employees have the potential resources to help them succeed. Gould-Werth et al (2018) found that employers with greater access to resources were better able to communicate and make more efforts to accommodate and retain employees with disabilities. This theme is consistent with other research showing that employers can challenge stereotypes and minimize bias towards people with disabilities (Lindsay et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, although a high proportion (81.5%) of people with and without disabilities who requested accommodations were granted or partially granted them, people with disabilities were even more likely to be fully granted accommodations [30]. Nonetheless, the characteristics of impairment causing the disability [32,33], disability severity [33][34][35][36], and disability onset [37,38] are differentially associated with a differential likelihood of receiving accommodations.…”
Section: Prior Research On Workplace Accommodationsmentioning
confidence: 99%
“…We hypothesized that individuals with disabilities, those who are older, and women are more likely to request accommodations, as these groups often experience a mismatch between their individual work-related needs and job demands [14,24,29,36,38,39,[57][58][59][60][61][62]. We also hypothesized that individuals with multiple minority identities might be less likely to request accommodations, including individuals with disabilities and those who identify as LGBTQ+.…”
Section: Research Questionsmentioning
confidence: 99%
“…Over time, this can lead to increased job stress, dissatisfaction, turnover, and long-term disability [12][13][14][15][16][17][18]. Persistent or intermittent symptoms and fluctuating dysfunction can challenge conventional workplace approaches to disability management and accommodation [11,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%